2014
DOI: 10.3389/fpubh.2014.00013
|View full text |Cite
|
Sign up to set email alerts
|

Do Personally Tailored Videos in a Web-Based Physical Activity Intervention Lead to Higher Attention and Recall? – An Eye-Tracking Study

Abstract: Over half of the Australian population does not meet physical activity guidelines and has an increased risk of chronic disease. Web-based physical activity interventions have the potential to reach large numbers of the population at low-cost, however issues have been identified with usage and participant retention. Personalized (computer-tailored) physical activity advice delivered through video has the potential to address low engagement, however it is unclear whether it is more effective in engaging particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 26 publications
0
45
0
1
Order By: Relevance
“…To our knowledge, no other existing studies have paired tailored written and tailored video materials within the context of a dietary intervention study. The fact that the TW + TV intervention achieved more lasting dietary changes than TW alone may be due to the visual nature of the video intervention creating better attention to the information that led to improved retention [ 50 ]. Alternatively, it could be due to the video intervention providing better motivation for lasting change than just reading the information, or it could be that the combination of the tailored written and tailored video created a synergy where the information in the different media complemented each other and enabled participants to achieve lasting dietary changes.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no other existing studies have paired tailored written and tailored video materials within the context of a dietary intervention study. The fact that the TW + TV intervention achieved more lasting dietary changes than TW alone may be due to the visual nature of the video intervention creating better attention to the information that led to improved retention [ 50 ]. Alternatively, it could be due to the video intervention providing better motivation for lasting change than just reading the information, or it could be that the combination of the tailored written and tailored video created a synergy where the information in the different media complemented each other and enabled participants to achieve lasting dietary changes.…”
Section: Discussionmentioning
confidence: 99%
“…Videos have been used in previous health behaviour change websites; however their contents have not been tailored to individual recipients, mainly because the videos were merely supporting other intervention components [ 21 – 23 ]. Pilot studies that informed the current study by Soetens et al [ 24 ] and Alley et al [ 25 ], have demonstrated initial efficacy for using tailored videos, with participants in the video group rating the acceptability of the advice significantly higher than those receiving text-based feedback; they also spent significantly more time on the website. However, the methodological limitations of these studies (e.g.…”
Section: Introductionmentioning
confidence: 86%
“…Alley et al . () compared the attention and recall outcomes of tailored physical activity advice in videos vs. the text format with 21 experimental group participants and 20 control group participants. Their results suggested that video‐tailored feedback attracted greater attention than did text‐tailored feedback.…”
Section: Introductionmentioning
confidence: 99%